Selangor licensees’ compliance behaviour towards the payment of local sales tax to the royal Malaysian Customs Department / Mohd Azahari Abdul Samad - Abdul Samad, Mohd Azahari (2014)
The objective of this study is to determine whether the licensees’ tax knowledge, sense of responsibility, time management and intention to evade tax have an impact on their local sales tax payment to the Royal Malaysian Customs Department. The major finding of the research has shown that most of the respondents were paid the high amount of local sales tax per year. Next, findings on licensees’ behaviour such as tax knowledge, sense of responsibility, time management and intention to evade tax have shown the positive, high and good relationship with the tax payment in general.In conclusion, the result of this study indicates that only positive and good behaviours among the licensees such as their tax knowledge and sense of responsibility can give the big impact and encourage to the high tax payment.